Kajian Ruang Budaya Nyadran Sebagai Entitas Budaya Nelayan Kupang di Desa Balongdowo - Sidoarjo - Sangadji, Faizal Ardiansyah; Ernawati, Jenny; Nugroho, Agung Murti (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
Balongdowo village Candi region is the location of the center of mussel shells fishing settlement located in Sidoarjo. Every year before the fasting month mussel fishing communities implement Nyadran cultural traditions that became their cultural space. Study of cultural space is done by using qualitative methods and supported by observation of behavior - environment and theory formation of cultural space. Results spaces formed culture is influenced by cultural traditions Nyadran ranging from the preparation stage, the departure, the disposal of a chicken , float an offering, a pilgrimage to the tomb of the Goddess Sekardadu, search demonstration mussel, and cover .Keywords : cultural space, Nyadran, mussel fishermen, Balongdowo